The Ministry of Agriculture, Livestock and Nutrition (MAGA) led the Local Technical Agroclimatic Committees (LTAC) officialization in Guatemala - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The LTACs development has led to their officialization in Guatemala in 2021 from the minister's office, which commits the participation of all departmental heads and central units of the ministry.